BINA-DAMAI DALAM KOMUNITAS PESANTREN: Sebuah Upaya Counter-Radikalisme - Mantu, Rahman (WALISONGO, 2015)
This article discussed about the experience of al-Qodir Boarding School in SlemanYogyakarta in the effort to counter the radicalism through the approach of peacebuilding. Applying qualitative approach, this research using the methods ofobservation and deep interview in collecting data. With the theoritical frameworkof cognitive peace building, three factors of peace building became the focus; themechanism of internal group, among group and external group. The mainresearch finding here was the essential role of kiai in building participativedialogue with the community out of the boarding school which was implementedthrough social actions. It resulted in the ability of al-Qodir Boarding School informulating the strategy of radicalism counter which became a typical strategy ofpesantren among so many strategies to find out new formulations in avoiding themovement of radicalism in Indonesia.***Tulisan ini akan membahas tentang pengalaman Pondok Pesantren Al-Qodirterhadap upaya counter-radikalisme melalui pendekatan bina-damai di SlemanYogyakarta. Penelitian ini menggunakan metode kualitatif dengan melakukanpengamatan serta wawancara mendalam. Kerangka teoritik yang digunakanpeneliti adalah teori peace building. Perdamaian menurut teori ini bisa terciptakarena tiga faktor; mekanisme internal, antar kelompok dan eksternal. Temuandari riset ini adalah adanya peran penting kiai dalam membangun dialogpartisipatif dengan masyarakat luar pesantren yang terimplementasi melaluiaksi-aksi sosial. Hasilnya Pesantren Al-Qadir mampu merumuskan strategicounter-radikalisme yang khas pesantren ditengah upaya banyak pihak mencariformulasi baru dalam menangkal gerakan radikalisme di Indonesia.